Microbial preparation for pesticide residues (chlorpyrifos ethyl) treatment in agricultural soil - Luong, Huu Thanh; Vu, Thuy Nga; Nguyen, Ngoc Quynh; Dam, Trong Anh; Nguyen, Thanh Lam; Tran, Thi Nhu Hang; Nguyen Kieu, Bang Tam (Hue University Journal of Science: Natural Science, 2025)
Chlorpyrifos ethyl (CPF), a widely used organophosphate pesticide, poses significant environmental risks because of its excessive application beyond recommended levels. This study presents the development of a microbial preparation (MP) for the treatment of CPF residues in soil using indigenous strains Methylobacterium populi (CNN2) and Ensifer adhaerens (VNN3), which were selected on the basis of their demonstrated CPF-degrading capability in prior research. The objective was to identify optimal conditions for biomass production to formulate a stable and effective MP. Laboratory-scale experiments were conducted to evaluate biosafety and determine ideal parameters, including pH, temperature, fermentation media, and inoculum ratio for microbial growth. The selected strains met European biosafety standards, exhibited mutual compatibility, and showed no antagonism toward beneficial microorganisms. Optimal biomass production was achieved at 30 °C and pH 6.5–7.0, in an SX1 medium with a 3% inoculum ratio. The strains demonstrated impressive in vitro CPF degradation capabilities, achieving up to 81% and 95% degradation efficiency for CNN2 and VNN3, respectively, after three days of cultivation. The developed MP maintained high viability with cell counts of 10⁹ CFU/g after one month, 10⁸ CFU/g after six months, and 10⁷ CFU/g after twelve months. These results demonstrate the potential of native, eco-friendly microbial agents for effective bioremediation of pesticide-contaminated agricultural soils.